2020
DOI: 10.9734/ajrcs/2020/v5i430102
|View full text |Cite
|
Sign up to set email alerts
|

Combining Ability and Heterosis for Some Yield Component Traits in a 10x10 Diallel Cross of Rice (Oryza sativa L.)

Abstract: A ten – parent diallel experiment was carried out at the Teaching and Research Farms of the Federal University of Agriculture, Makurdi, Nigeria, to estimate combining ability and heterosis in rice. The design was a 10x10 alpha lattice with three replications and data was collected on plant height (PH), tiller numbers/plant (TN), leaf length (LL) and width (LW), days to flowering (DF), panicle length (PL), panicle exsertion (PE), spikelet numbers/panicle (SN), 100 seed weight (100SW) and days to maturity(DM). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 7 publications
6
3
0
Order By: Relevance
“…Therefore, the former genotypes can be used in the hybrid rice breeding program and the rice breeding program as good combiners and donors for heavier grain weight. These findings were agreed with those obtained by Awad-Allah 12 , Sari et al 25 , Vange et al 26 and Rasheed et al 27 . Grain yield per plant data showed that the parental varieties Giza 178 R (4.7) and BR 7414-22-1 (2.8) gave positive highly significant (desirable) values of general combining ability (GCA) effects.…”
Section: Concerning Genotypessupporting
confidence: 93%
See 3 more Smart Citations
“…Therefore, the former genotypes can be used in the hybrid rice breeding program and the rice breeding program as good combiners and donors for heavier grain weight. These findings were agreed with those obtained by Awad-Allah 12 , Sari et al 25 , Vange et al 26 and Rasheed et al 27 . Grain yield per plant data showed that the parental varieties Giza 178 R (4.7) and BR 7414-22-1 (2.8) gave positive highly significant (desirable) values of general combining ability (GCA) effects.…”
Section: Concerning Genotypessupporting
confidence: 93%
“…The highest values were shown in the crosses, IR 58025 B/G 46 B (76.2), Ghaiya/Sakha 101 (65.7), BR 7414-22-1/Sakha 101 (55.0), BR 7414-22-1/IR 58025 B (30.2) and IR 69625 B/Ghaiya (30.0). These results are similar to the results obtained by Cui et al 24 , Sari et al 25 , Vange et al 26 and Rasheed et al 27 . Concerning the number of filled grains/panicle, data in Table 8 showed that nine crosses showed significant and highly significant positive values of SCA effects.…”
Section: Concerning Genotypessupporting
confidence: 92%
See 2 more Smart Citations
“…On the contrary, nine hybrids had significantly negative heterosis. For grain yield, eight hybrids had positive significant heterosis Similar results were obtained by Sarker et al, 2002;Gnansekaran et al (2006) and Vange et al (2020) Concerning milling recovery characters, only one cross showed significant and positive best-parent heterosis for hulling% and head rice% (Giza 178 x IET1444 and Sakha 105x Giza 178), respectively. Meanwhile, Sakha 105x Sakha 106 gave positive best-parent heterosis for gelatinization temperature.…”
Section: Heterosis Relative To Better Parentsupporting
confidence: 84%